A PROSPECTIVE STUDY ON THE CLINICO-RADIOLOGICAL AND FUNCTIONAL RESULTS OF FIXING ACETABULAR FRACTURES WITH QUADRILATERAL PLATE INVOLVEMENT USING INTRAPELVIC REDUCTION AND BUTTRESS PLATE VIA MODIFIED STOPPA TECHNIQUE - Rahul, Kumar; Akash, Anant; Agrawal, Nilesh Kumar; Kumar, Santosh (Student's Journal of Health Research Africa, 2024)
Background To achieve the best outcomes, precise reduction in anatomy, fixation of the firm, and rehabilitation are required. The most significant weight-bearing joint in the hip joint, and its fracture is intra-articular is the acetabulum. Several authors have suggested innovative fastening techniques to address these issues, such as an infra pectineal plate and many unique quadrilateral surface buttresses or spring plates to support the quadrilateral plate. Objectives The objective of this study was to assess instances of quadrilateral plate acetabular fractures that were treated with internal fixation and open reduction. Materials and methods The study was a prospective study that was performed at the Indira Gandhi Institute of Medical Sciences (IGIMS), Patna, Bihar, India. The study was conducted from July 2023 to June 2024. Overall, 20 participants were enrolled in the study. Results The participants' age in this study was 39.2 ± 11.1 years on average. Most of the enrolled participants were male. On the right side of 11 (%) hips and the left side of 09 (%) hips, all fractures were unilateral. 05 (%) patients experienced a fall from a height, 07 (%) patients were run over by a pedestrian, and 08 (%) patients were involved in motor vehicle accidents. The surgery took an average of 154 ± 29.1 minutes. Conclusion The outcome of the study was that it was a simple, secure, and effective surgical method for pelvic stabilization in carefully selected patients with a quadrilateral plate of acetabulum fractures, which is shown to be reduced openly and fixed internally. Recommendation Open reduction and internal fixation were shown to be a better approach. Furthermore, future investigations may result in the assurance of use of the open reduction and internal fixation for acetabular fractures.